AB0986 Electromyography and Biochemistry Characterization of Patients with Pain and Muscle Weakness - Extended Cohort. (10th June 2014) - Negru, M.M.; Berghea, F.; Dimitrakopoulos, C.; Balanescu, A.; Bojinca, V.; Opris, D.; Saulescu, I.; Groseanu, L.; Predeteanu, D.; Ionescu, R.
Abstract : Background: Muscle damage, often manifested as muscle weakness and, rarely as muscle pain is common in rheumatic diseases. These include idiopathic inflammatory myopathies (IIM), and myopathy seen in other rheumatic diseases, such as rheumatoid arthritis. Electromyography is an standardized and reproductible method for positive diagnosis of muscle disease. Objectives: The aim of the present study is the analysis of subjective signs such as weakness and pain in relation to the changes observed in EMG (taking as parameters the duration, the amplitude and extent of polyphases of motor unit potentials - MUPs) and biological data. Methods: The study is prospective, randomized.The study was done on 25 subjects presented in the Clinic of Internal Medicine and Rheumatology Hospital, "St. Maria", Bucharest for weakness and muscle pain, which for positive diagnosis we conducted EMG using concentric needle - method for performing MUP (motor unit potential) and quantitative analysis of multi-MUP. Like parameters were used amplitude and duration and degree of poliphases MUP. Values were interpreted in relation to age and studied muscles. SPSS 19.0 have been used to perform statistical analysis.Data are presented in mean (sd) format; a p<0.05 was considered significant Results: The study group comprised 32% men and 68% women. mean age (SD) - 52.1 (12.6).The average age (SD) of the disease was 5.6 ( 7.1). I noticed that those with longer duration of disease were more frequently with impaired inferior limb and impaired superior limb did not differ from those with less seniority than those with long standing disease. Those with severe impaired inferior limb have a degree of MUPs poliphases for tibialis anterior muscle lower (4) vs. 21 how is the average in those without involvement of inferior limb.Those with severe impaired superior limb have a duration of MUP to interosseous muscle lower (6.4 to 8.5 affected from unaffected) and a degree of poliphases of MUP lower (2 versus 8.6 unaffected) in the same muscle. As the duration of the disease is higher the score of muscular testing is greater.Lower score in muscle testing means higher CK and LDH. Were positively correlated (Pearson index =0.666, p<0.001) higher values of ESR, and muscle weakness (Pearson index =0.455, p<0.05) with the degree of polifazism of PUM. The high values of the enzymes of muscle's cytolysis were negatively correlated with the duration of PUM (Pearson correlation index= -0.547, p<0.001 for LDH, Pearson correlation index = -0.463, p<0.05 for CK). Also high LDH values were negatively correlated (Pearson correlation index = -0.529) and statistically significant (p<0.001) with the amplitude of MUP. Conclusions: Electromyography is therefore an objective method for the characterization of patients with pain and muscle weakness. References: Aeronautical Medical and Psychology Revue, vol.17, 2013, 4(65), Correlations between electromyographic data and clinical and biological changes on a lot of patients with pain and muscle weakness - prospective study, Maria-Magdalena Negru, Daniela Anghel, Vasilia Iorgoveanu, Florian Berghea, Ruxandra Ionescu. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5935